How Do Binus University Freshmen Appraise English Entrant? (A Qualitative Approach) - Almodad Biduk Asmani (Humaniora, 2014)
The research examined the assessments and the comments provided by Binus University freshmen students concerning their study experiences of taking University English Entrant as part of their compulsory English course program at Binus during the odd semester of 2010/2011. The goals of the research were to find out whether such program had been useful and effective for these students in terms of the teaching quality, course contents, and independent learning system commonly applied at Binus University. The research applied the technique of qualitative approach with the focus on finding the general feedback of these students in evaluating the program based on free-response data. In the initial stage of the research, the writer selected the random sample of four to five English Entrant classes ranging from small to large number of students. The writer then distributed the questionnaires to the subjects. After the data had been collected, the writer tabulated, summarized, and interpreted the data in the discussion. The final result indicates that communicative teachers are always the best preference; communicative tasks that put emphasis on fluency and clarity, rather than accuracy, have always been appreciated highly; and feedback in learning is highly expected for the independent learning system.